1992
DOI: 10.1117/12.130486
|View full text |Cite
|
Sign up to set email alerts
|

<title>Chemical composition of TiNxOy solar selective absorbers</title>

Abstract: TiNXOY films were prepared by activated reactive evaporation (ARE) [1J on copper to produce a tandem solar absorber exhibiting a low emissivity c(250 °C) 0.05. The optical selectivity of the absorber is determined by the preparation conditions. Coatings deposited with different nitrogen to oxygen (pN2 /po2) gas pressure ratios, show that maximum c is obtained when the ratio PN2 /po2 is held 8. The chemical composition of these TiNXOY films was determined by x-ray photoelectron spectroscopy (XPS) and related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The experiments did not lead to film degradation which is prevented by the Si02 barrier film. This has been confirmed by XPS measurements under UHV conditions [14], where only the Ti02 signal decreases little in time but TiN and TiO signals remained constant. Although (t9 > 600) of tempered samples is greater than before treatment its contribution to the hemispherical emittance remains small due to the cos(t9) factor.…”
Section: Tempered Coatingssupporting
confidence: 59%
See 2 more Smart Citations
“…The experiments did not lead to film degradation which is prevented by the Si02 barrier film. This has been confirmed by XPS measurements under UHV conditions [14], where only the Ti02 signal decreases little in time but TiN and TiO signals remained constant. Although (t9 > 600) of tempered samples is greater than before treatment its contribution to the hemispherical emittance remains small due to the cos(t9) factor.…”
Section: Tempered Coatingssupporting
confidence: 59%
“…Normal emittance of copper is increased by 0.05 when covered with 100 nm TiNXOY (see fig.8, 'copper' and 'as received'). Evidence for Ti2N has been obtained by a peak at 78.4 0 However this phase was not observed in XPS measurements [14]. The measured maximum at 82 °i s considerably higher than calculated which is not yet understood.…”
Section: Untreated Coatingsmentioning
confidence: 85%
See 1 more Smart Citation
“…Using an antireflecting coating instead of roughness has the advantage of achieving a steeper rise of reflectance at This explains the lower emittancies observed in the presented films compared to the emittancies of rough ones [1 1] . Eitle et al [31] observed on uncovered TiNZOY a change from more dielectric to metallic behavior (i. e. rise in k) when examing the films at 400 °C in vacuum. In contrast we have no possibility to produce predicted rough surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been previously observed that the composition of Zr-O-N films from literature was localized in a very specific region of the Zr-O-N ternary diagram [17] , which could explain the observed color restrictions. Titanium oxynitride coatings are also used in a broad range of applications such as solar collector devices [18,19], diffusion barriers [20,21], isolation films in metal-isolatormetal structures [21], wear resistance coatings [22], among others. In terms of decorative applications TiN films are known for their golden appearance [23,24], and ranges of colors from metallic grey to gold and red brownish were also reported in TiN films [25].…”
Section: Introductionmentioning
confidence: 99%